Pengaruh Penguasaan Teknologi Informasi Digital dan Pengetahuan Manajemen Terhadap Kinerja Driver Go-jek Online (Studi Kasus Komunitas Oktouber Surabaya) - Mauludi, Achmad; Wispandono, Mochammad (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This study aims to analyze and determine the effect of Mastery of Digital Information Technology and Management Knowledge on Gojek Driver Performance in the Surabaya Oktouber Community. This research uses quantitative research. The sampling technique used is random sampling. The total population is known to be 300 people and the result obtained using the slovin formula is 75, so in this study the sample set is 75 driver. Data was collected through questionnaires and tested with data instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination tests. All of these tests were carried out using the SPSS (Statistical Product and Service Solutions) 21 for Windows program. The results showed that mastery of digital information technology has a positive and significant effect on the performance of Gojek drivers. Management knowledge has a positive and significant effect on the performance of Gojek drivers. And mastery of information technology and management knowledge together (simultaneously) have a positive and significant effect on the performance of Gojek drivers in the Surabaya Oktouber community.